TREATMENT OF SENILE ENTROPION: A COMPARISON OF STANDARD AND MODIFIED SURGICAL TECHNIQUE - Qurban, Qirat; Kamil, Zeeshan (Journal of Ayub Medical College Abbottabad, 2022)
Background: The aim of this study is to compare the postoperative functional outcomes of two different surgical techniques for the correction of senile lower lid entropion. It was a Quasi experimental study, carried out at BHY Hospital, Karachi, Pakistan from January to December 2018. Method: This study recruited fifty patients belonging to either gender with an age range of 60-70 years having unilateral lower lid senile entropion. All the patients were briefed about the study dynamics and divided into two groups with twenty-five patients in each group via convenience-based sampling technique. Those with a prior history of lid surgery or bleeding diathesis were excluded from the study. Patients of group A underwent the standard Weis surgical procedure whereas Group B patients underwent a modified surgical approach using an external tamponade. Main outcome measure was the rectification of abnormal lid position to the normal level. All the patients were followed for a period of six months postoperatively. Study approval was obtained from the institutional ethical review board. Result: This study included a total of fifty patients with twenty-five patients in each group. Mean age was 64.5±3.23 years. Recurrence was observed in 32% patients of group A and 4% patients of group B. Conclusion: The modified surgical technique for entropion repair using an external tamponade has a favourable outcome with minimal recurrence and symptomatic relief.